2022
DOI: 10.3390/ijerph192315463
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression, Anxiety, and Stress in Junior High School Students in Guadalajara, Mexico: A Cross-Sectional Survey Study

Abstract: Confinement and a lack of social interaction are associated with depressive symptoms, low self-esteem, and suicidal thoughts. We report the results of a cross-sectional survey of 1414 junior high school students. The aim was to evaluate the prevalence of depression, anxiety, and stress in Guadalajara, Mexico, during the COVID-19 pandemic. Mean scores on the validated Spanish version of the Depression, Anxiety, and Stress Scale (DASS-21) were found to be 6.15 ± 5.6 for depression, 5.8 ± 5.2 for anxiety, and 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A recent systematic review reported that increasing rates of COVID-19 infection, combined with associated factors, had caused an increase in the prevalence of major depressive disorder [3]. There was an increased number of children and adolescents displaying depressive symptoms during the COVID-19 pandemic [4,5]. According to the National Health and Morbidity Survey 2019, an estimated 2.3% of Malaysia's adult population, or half a million people, suffered from depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reported that increasing rates of COVID-19 infection, combined with associated factors, had caused an increase in the prevalence of major depressive disorder [3]. There was an increased number of children and adolescents displaying depressive symptoms during the COVID-19 pandemic [4,5]. According to the National Health and Morbidity Survey 2019, an estimated 2.3% of Malaysia's adult population, or half a million people, suffered from depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both forms of stress exert different effects on the human body 2,3 . Globally, the prevalence of depression is 10% and anxiety is 33% between the ages of 18 and 25 years 4 . Different results described the prevalence of stress in turkey (27%), the UK (45%), Nepal (20.9%), India (63.5%), Bangladesh (54%) and Malaysia (41%) mentioned in the study 5 .…”
Section: Introductionmentioning
confidence: 99%